Climate oscillation and the invasion of alien species influence the oceanic distribution of seabirds. Issue 17 (20th August 2020) - Perez‐Correa, Julian; Carr, Peter; Meeuwig, Jessica J.; Koldewey, Heather J.; Letessier, Tom B.
Abstract: Spatial and temporal distribution of seabird transiting and foraging at sea is an important consideration for marine conservation planning. Using at‐sea observations of seabirds ( n  = 317), collected during the breeding season from 2012 to 2016, we built boosted regression tree (BRT) models to identify relationships between numerically dominant seabird species (red‐footed booby, brown noddy, white tern, and wedge‐tailed shearwater), geomorphology, oceanographic variability, and climate oscillation in the Chagos Archipelago. We documented positive relationships between red‐footed booby and wedge‐tailed shearwater abundance with the strength in the Indian Ocean Dipole, as represented by the Dipole Mode Index (6.7% and 23.7% contribution, respectively). The abundance of red‐footed boobies, brown noddies, and white terns declined abruptly with greater distance to island (17.6%, 34.1%, and 41.1% contribution, respectively). We further quantified the effects of proximity to rat‐free and rat‐invaded islands on seabird distribution at sea and identified breaking point distribution thresholds. We detected areas of increased abundance at sea and habitat use‐age under a scenario where rats are eradicated from invaded nearby islands and recolonized by seabirds. Following rat eradication, abundance at sea of red‐footed booby, brown noddy, and white terns increased by 14%, 17%, and 3%, respectively, with no important increase detected for shearwaters. Our results have implication for seabird conservation and island restoration. Climate oscillations may cause shifts in seabird distribution, possibly through changes in regional productivity and prey distribution. Invasive species eradications and subsequent island recolonization can lead to greater access for seabirds to areas at sea, due to increased foraging or transiting through, potentially leading to distribution gains and increased competition. Our approach predicting distribution after successful eradications enables anticipatory threat mitigation in these areas, minimizing competition between colonies and thereby maximizing the risk of success and the conservation impact of eradication programs. Abstract : Climate oscillations may cause shifts in seabird distribution, possibly through changes in regional productivity and prey distribution. Invasive species eradication and subsequent island recolonization can lead to predictable distribution gains and increased competition. Our analysis predicting range extension after successful eradications enables anticipatory threat mitigation in these areas, minimizing competition between colonies, and thereby maximizing the risk of success and the conservation impact of eradication programs.